A COMPARATIVE STUDY BETWEEN ATROPINE AND TROPICAMIDE AS CYCLOPLEGIC AGENTS FOR A SAMPLE OF IRAQI CHILDREN (Iraqi Journal of Medical Sciences, 2019)
Background: A perfect cycloplegic medication which is viable, nontoxic, and helpful permitting precise estimation of the refractive errors by objective and/ or subjective tests isn't yet accessibleObjective:This trial was designed to evaluate the cycloplegic activity and adverse effects of two cycloplegic agents (atropine vs. tropicamide) for children with hyperopia. The response to cycloplegia in different age groups, with or without strabismus, was also compared.Methods: Tropicamide 1% eye drops (Regimen 1) and Atropine 1% eye drops (Regimen 2) was evaluated in thirty children with different ages. Cycloplegic refractions and adverse effects were assessed. The results expressed refractions and presented as mean ± SD. A P-value of less than 0.05 was considered statistically significant.Results: Tropicamide refraction mean value (+3.60 ± 2.25 D) didn’t differ significantly in comparison with that of atropine (+3.92 ± 2.50 D); (P >0.05). Children during regimen 2 (atropine drops) suffered from more frequent and statistically significant side effects (p
Keywords: Cycloplegia Hyperopia Atropine Tropicamide